Perancangan Tata Cahaya pada Interior Rumah Tinggal - Dila Hendrassukma (Bina Nusantara University, 2014)
Homestay is a place where each individual coming back after doing her/his routine and non-routine daily activities. A good residential interior design would enhance the quality of life of its inhabitants. The majority of Indonesian population, Jakarta in particular, has been aware of the importance of designing their home interior properly. However, home interior lighting, which is key to successful design of an interior space, is often under-emphasized. Research tried to collect lighting techniques often used in residential interiors. The result is a brief explanation and easy to apply regarding the types of information that can be used to illuminate any activity on the interior of the residence. Qualitative method by literature study is used in the making of this research.